Leading-edge tubercles delay flow separation for a tapered swept-back wing at very low Reynolds number - Wei, Zhaoyu (2020)
Flow separation characteristics for two tapered swept-back wings, one with straight leading-edge (LE) and the other with tubercled LE, were investigated in a water tunnel using time-resolved particle image velocimetry (TR-PIV) technique. The two wings were based on the SD7032 aerofoil profile, with Reynolds number Re = 1.4 × 104, close to the working condition for common underwater gliders. The LE tubercles were designed such that the amplitude decreased linearly from the wing root to wing tip, while retaining constant wavelength. Results indicate that the baseline wing shows significantly separated flow in the outboard region at pitch angle of 10° and 20°, and the flow remains attached in the inboard region due to relatively larger local Reynolds number. Implementation of LE tubercles can mitigate flow separation downstream of both troughs and peaks. At higher pitch angles, the separated flows cover most of the baseline wing surface, whereas flow remains attached downstream most of tubercle peaks. Streamwise aligned counter-rotating vortex pairs (CVPs) formed over the tubercles are significantly tilted and asymmetrical due to the sweep and amplitude difference between the two sides of tubercle. Consequently, weaker vortices in CVPs close to the wing root are rapidly dissipated, allowing the CVPs to evolve into a series of co-rotating vortices (CVs), which exerted significant impact on flow separation characteristics downstream of the tubercles.